Critical role of digitalization within the drug intervention ecosystem among technical, vocational education and training (TVET) students: A systematic review. - Kamarul Arifain, Siti Marhamah; Abdullah, Nurhanim Saadah; Abd Rahim, Siti Noor Fauziah; Ismail, Mohd Noorasri; Abdullah, Nurul Hidayah Liew; Hamzah, Norkhairolizah; Ismail, Norismaliza (Journal of Ethnicity in Substance Abuse)
Substance use and addictive behaviors are a major public health concern, with prevalence peaking among emerging adults, including those in and vocational education training (TVET) students. Traditional interventions face significant challenges, such as low perceived need for treatment, concerns about stigma, and limited resources for face-to-face delivery to large student populations. Digitalization offers a highly scalable and discreet alternative to overcome these barriers. This systematic review synthesizes evidence regarding the effectiveness and design of Technology-Based Interventions (TBIs) targeting substance use among TVET students. Overall, TBIs demonstrate effectiveness in reducing substance use and related consequences in emerging adults/college students. Digital programs developed for vocational students, such as "Meine Zeit ohne," have shown small but significant effects in reducing overall adverse health behaviors and problematic Internet use. The critical role of digitalization is realized through the systematic integration of behavioral science frameworks, such as the Behavior Change Wheel (BCW) and User-Centered Design (UCD), to deliver targeted interventions such as Personalized Normative Feedback (PNF) and training in mindful decision making. Despite the promise, challenges persist, notably high attrition and the need for more robust effectiveness data on illicit drugs and newer digital technologies (e.g., social media, AI).